Seasonal Rooting Response of Stem Cuttings of some Forest Tree Species to Auxins - Nanda, K. K.; Purohit, A. N.; Bala, Adarsh; Anand, V. K. (Indian Forester, 1968)
Rooting response of stem cuttings of 35 tree species to different auxins during different seasons was investigated. The results show that (i) Plant species vary markedly in their ability to root. Some root easily, others with difficulty and still others do not root even with auxin application; (ii) Planting season has a pronounced effect on rooting of cuttings and the effect appears to be correlated with seasonal changes in cambial activity during the annual cycle; and (iii) The effectiveness of auxins on rooting of cuttings varies with the season. An auxin may stimulate rooting of a plant species in one season but may inhibit it in other season. Again maximum rooting of the same plant species may be caused by two different auxins in two different seasons. The results are discussed in the light of available literature on the subject.